Characterization of the complete mitochondrial genome of Stenopsyche angustata (Trichoptera, Stenopsychidae) - Jing-Cai Huang; Xiao-Xue Wang; Xi-Fa Zhong; Yi-Min Li; Hong-Lin Qin; Yu-Jun Wang; Hong Wang (Mitochondrial DNA. Part B. Resources, 2020)
Caddisflies of Stenopsyche angustata (Trichoptera, Stenopsychidae) are widely distributed in various freshwater bodies and a few species inhabit marine environments. The mitochondrial genome was sequenced by Illumina high-throughput sequencing, and then the complete mitochondrial genome sequence was obtained through splicing and assembly. The mitochondrial genome sequence size was 15,371 bp, comprising 13 protein-coding genes, 22 tRNA genes, two rRNA genes, and a control region. Two of the protein-coding genes (COX 2 and nad 5) had an incomplete termination codon T. In addition, the start codon of all protein-coding genes was ATN, except for the start codon of the nad4l gene which was GTG. The base composition of the mitochondrial genome was 41.64% A, 35.03% T, 7.81% G, and 15.52% C.